Public Service Innovation Population Administration Service System in Inland and Border Areas North Kalimantan (SIPELANDUKILAT) - Ahmad, Muh. Syarif; Rahman, Aulia (KnE Social Sciences, 2022)
Border areas and new expansion areas are both often undeveloped areas, with limited facilities and infrastructure, far from urban centers or government, and with high inequality and poor availability of public services. In 2019, Sipelandukilat won the Top 45 Innovation award from the Ministry of State Apparatus Utilization and Bureaucratic Reform (KEMENPANRB). The purpose of this study was to describe the Sipelandukilat service innovations and identify the supporting and inhibiting factors of this innovation program. Descriptive qualitative methods were used, with data source triangulation. The results demonstrated that the implementation of the Sipelandukilat innovation program has gone well, although improvements are needed, especially for areas that have limited internet networks. There were eight factors driving the development of the Sipelandukilat innovations, but financial and demographic factors were the most important. Meanwhile, there were two factors that hindered the innovations, namely the risk aversion cultural factor and the inability to deal with risk and change. Keywords: new expansion areas, innovation attributes, supporting and inhibiting factors of innovation.